Development of dehydrated candied saba (Musa sapientum Linn. var. Compressa) - Quijano, Ana Marie Mangulabnan; Francisco, Ma. Leonora dL. (1994.)
Dehydrated candied saba was developed using the step-up method, 45-55-65 Brix, of candying and then cabinet drying sliced nd sulfited, water-blanched, and water-blanched and sulfited) and levels of composition of syrup. Composition of syrup involved varying the glucose-sucrose ratio to 0% glucose-100% sucrose, 10% glucose-90% sucrose, 20% glucose-80% sucrose, and 30% glucose-70% sucrose. Both objective and subjective evaluations were made to determine the effects of the variables on the quality characteristics of the finished product. Results of sensory evaluation indicated that the best dehydrated candied saba can be produced from the one pre-treated by steaming and sulfiting and stepped-up to a syrup composed of 30% glucose-70% sucrose. Characteristics of the product were yellow in color, firm in texture, with a moderate saba flavor and an ideal sweet taste. It was given a like moderately rating in terms of general acceptability.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Banana; Banana, Candied